Fisiologia, metabolismo antioxidante e conservação pós-colheita de mamão ‘sunrise solo’ sob combinações de solventes naturais euteticos profundos com recobrimentos de fécula de mandioca - Sousa, Alex Sandro Bezerra de (2018)
Biodegradable coatings are a low-cost and sustainable technology, such as those based on cassava starch. these need to be incorporated into technologies that make them not only efficient in postharvest conservation of fruits, but also stable and innocuous to humans. Based on that, natural deep eutectic solvents (NADES) are made from natural, non-toxic components and have great potential in the conservation of fruits, such as oxalic acid. In addition, the NADES consist of innovative technology because they have plasticizer properties, being able to replace the glycerol, plasticizer most used in coatings based on natural polymers. Papaya is a highly consumed fruit due to the presence of antioxidant compounds, but it is highly perishable, presenting fast quality depreciation during postharvest. The understanding of the physiological processes and the dynamics in the antioxidant metabolism can generate bases for the development of technologies aimed at enhancing of the postharvest life and maintaining the stability of the antioxidant agents. This study was divided into two experiments. The first one aimed to evaluate the physiology and postharvest conservation of papaya under association of NADES of choline chloride and oxalic acid with cassava starch-based coatings (SNADES) during the storage under room conditions. The second experiment aimed to evaluate the effect of the application of SNADES on bioactive compounds and the antioxidant metabolism of 'Sunrise Solo' papaya during the storage under environmental conditions. The ‘Sunrise Solo’ papaya fruits were harvested and transported to the LBTPC /CCA /UFPB, where they were washed, sanitized and submitted to the edible coating. The experiment was performed in CRD, factorial 4x6 being 4 edible coating (SNADES, cassava starch associated with NADES plus sweet orange essential oil (NADES + O), associated cassava starch with glycerol (S + Gly) and uncoated fruits (C) ) and 6 periods of evaluation (0, 2, 4, 6, 8, and 10 days) during storage in the ambient condition. The fruits coated with SNADES presented a decrease in the respiratory rate, with a delay of 3 days when compared to the fruits coated with SNADES + O and SGly, presented a longer delay in the development of the yellow color, and maintained firmness for a longer period, indicating a delay in the ripening. The use of SNADES also provided tastier fruits and of excellent appearance. The SNADES coated papayas presented better efficiency in the H2O2 capture, being correlated with the higher activity of the CAT and APX enzymes at the beginning of the storage, which indicates fruits in better state of quality conservation. SNADES also provided better functional quality papayas with higher extractable phenolic contents and higher antioxidant activity by DPPH• . These data demonstrate that the NADES of choline chloride and oxalic acid has the potential to be incorporated into the polymer matrix as a plasticizer and functional agent for the maintenance of quality and maturation delay, extending the postharvest life of papaya during storage under environmental conditions, as well as improving the efficiency of the enzymatic antioxidant system and the increase of bioactive compounds and antioxidant activity.